INTERKONEKSI PTKIS DAN BMT NU DALAM MENDUKUNG PEMBANGUNAN EKONOMI LOKAL MELALUI BUMDESMA BERBASIS TATA KELOLA KEUANGAN SYARIAH DI CERMEE BONDOWOSO - Makki, Mustaqim; Miftah, Zaini (STAI Nurul Huda Kapongan Situbondo, 2023)
Higher education institutions are required to contribute to the development of science and solve social or economic problems faced by society by conducting collaborative research with industry partners or other institutions by involving lecturers and students and the community. Higher Education partnerships with related agencies certainly refer to the good relations that have been built with the concept of interconnection with the community. Guided by the Research and Community Service Road Map that has been designed by LP2M through an MoU with several institutions, including: BMT NU (Baitul Mall Wat Tamwil - Nuansa Ummat), NU Care - Lazisnu and Non-Governmental Organizations. Integration of partnerships built by universities with several institutions as academic activities of student lecturers in realizing the Tridarma of Higher Education such as KKN, PPL and Community Service and Research to develop scientific treasures. In the university's partnership with BMT NU or Baitul Mal Wattamwil NU in the management of Bumdesma funds, the PAR approach can be used to involve all relevant parties directly. Students and members of the local community can work together to plan strategies for using funds, find Bumdesma problems, and find creative solutions. The involvement and presence of universities in Bumdesma mentoring can provide benefits for campuses, financial institutions, Bumdes and Bumdesma managers and the wider community. The success of Bumdesma is largely determined by the ability of its management to manage the organization and activities carried out, so that the products and services produced have a comparative advantage over competitors. Therefore, good and careful planning is needed to be able to achieve Bumdesma's goals even in an uncertain business environment. Good planning Village business entities must be economical, efficient and effective.